La política cultural en el soft-power chino y su proyección en América Latina: análisis comparado de Ecuador y Brasil, 2008-2019 - Merlo Abad, Luis Alejandro (2022)
This thesis supports a comparison between the bilateral relationship of the People's Republic of China (hereinafter, P.R.C.) with the Republic of Ecuador and the P.R.C. with Brazil starting from the perspective of the soft-power theory developed by Joseph Nye Jr. that was later reworked according to the characteristics and interests of the P.R.C. and that constitutes the Chinese soft-power; In the same way, the edges of these relations are addressed from the perspective of economic power and the cultural influence displayed by the R.P.Ch. as a global power that exercises its leadership also in the developing world. Thus, the results of the investigative work delve into the degree of bilateral commitment until evidencing the degree of application of Chinese soft-power in each of the proposed country cases.